Library practice in hospitals: a basic guide, editado por Harold Bloomqvist, Alan M. Rees, Norman S. Stearns e Helen Yast: - Lemos, Antônio Agenor Briquet de (Revista de Biblioteconomia de Brasília, 1974)
BLOOMQVIST, Harold; REES, Alan M.; STEARNS, Norman S.; YAST, Helen de (Eds.). Library practice in hospitals: a basic guide. Cleveland: The `Press of Case Western Reserve University, 1972. 344 p. (ISBN 0-8296-0227-0)